Assessment of the Toxicological Effects of Pesticides and Detergent Mixtures on Zebrafish Gills: a Histological Study - Thamyris Santos-Silva; Rosy Iara Maciel de Azambuja Ribeiro; Stênio Nunes Alves; Ralph Gruppi Thomé; Hélio Batista dos Santos (Brazilian Archives of Biology and Technology, 2022)
Abstract Pesticides, as Temephos and Roundup, and surfactants, like Sodium Dodecyl Sulfate (SDS), when discharged into the environment, are harmful to non-target wildlife, especially fish. To evaluate the effects of those chemicals alone and their binary combinations, we assessed the histological alterations in Danio rerio gills after 15 days of exposure to Temephos (1ppm), Roundup (10ppm), SDS (2ppm), SDS plus Temephos (2ppm+1ppm), SDS plus Roundup (2ppm+10ppm) and Temephos plus Roundup (1ppm+10ppm). Hyperplasia, a regressive change, was significant in all exposed groups. The progressive change, complete fusion of lamellae, was significantly intensive in Roundup plus Temephos group. Regarding circulatory disturbances, vascular congestion was significant intensive in SDS group, while severe aneurysm was observed in Roundup group. Although xenobiotics in the blend are biologically complex, mainly for long periods, combinatorial exposure incremented only complete fusion of lamellae. Our results reinforce the rationalization of indiscriminate use of those compounds alone or in combination.